2019
DOI: 10.1002/pip.3174
|View full text |Cite
|
Sign up to set email alerts
|

Control of the STC power in PV modules' supplies for utility scale plants

Abstract: This article presents a specific procedure to control the standard test conditions (STC) power in photovoltaic (PV) modules. It also shows the results of its application on a supply of approximately 700 000 multicrystalline p‐type silicon BSF technology PV modules made by a worldwide known manufacturer (Tier‐1, Q4 2015). First, during the manufacturing process, the analysis of the STC power measurements of the whole supply carried out by the modules' manufacturer is included, where the quality of these measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…They are low and tend to decrease as the module mass production progresses. For example, σP MPP PMPP was found to be about 2-3% in modules manufactured around 1990 11 and about 0.5% in modules manufactured around 2015 16 Actual mismatch loss in situ and in operating arrays can be greater due to non-uniformity T C -differences between the modules of the same array may reach over 10 C in standard PV generators 17,18 ; the relationship between field performance and measured performance under simulated light that can make the actual variability greater than that deduced from the flash-reports; and the nonuniformity of illumination, especially in the case of bifacial generators because of the incident irradiance on its rear side, is usually nonuniform. This has been the object of recent studies 19,20 which concluded that the MML resulting from this non-uniformity is usually less than 0.3% in practical PV systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are low and tend to decrease as the module mass production progresses. For example, σP MPP PMPP was found to be about 2-3% in modules manufactured around 1990 11 and about 0.5% in modules manufactured around 2015 16 Actual mismatch loss in situ and in operating arrays can be greater due to non-uniformity T C -differences between the modules of the same array may reach over 10 C in standard PV generators 17,18 ; the relationship between field performance and measured performance under simulated light that can make the actual variability greater than that deduced from the flash-reports; and the nonuniformity of illumination, especially in the case of bifacial generators because of the incident irradiance on its rear side, is usually nonuniform. This has been the object of recent studies 19,20 which concluded that the MML resulting from this non-uniformity is usually less than 0.3% in practical PV systems.…”
Section: Introductionmentioning
confidence: 99%
“…Statistics on the distribution of I-V characteristics of a set of commercial modules under Standard Test Conditions, STC, have been available for many years, and the relationship between the MML and this information has been studied by several authors with the main objective of addressing whether the performance of the array can be improved by pre-sorting the modules or cells. [9][10][11][12][13][14][15][16] That was a relevant question years ago when modules were typically delivered to the market with MPP power under Standard Test Conditions, P Ã MPP , at ±10% around the specified nominal value. However, commercial modules are now classified in such a way that this range has been drastically reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Statistics on the distribution of I-V characteristics of a set of commercial modules under Standard Test Conditions, STC, have been available for many years, and the relationship between the 𝑀𝑀𝐿 and this information has been studied by several authors with the main objective of addressing whether the performance of the array can be improved by pre-sorting the modules or cells [16], [17], [59], [77]- [81].…”
Section: Mismatch Lossesmentioning
confidence: 99%
“…ratio between the corresponding standard deviation and the mean value for voltage, current and power, respectively), are low and tend to decrease as the module mass production progresses. For example, 𝐶𝑉 𝑃 M was found to be about 2-3% in modules manufactured around 1990 [16], and about 0.5% in modules manufactured around 2015 [17] using multicrystalline Si BSF (Back Surface Field) technology, and it is certainly still lower at present with increased production and monocrystalline Si PERC (Passivated Emitter and Rear Cell) technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation